2021
DOI: 10.1001/jamasurg.2021.0906
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With Surgery vs Functional Bracing for Patients With Closed, Displaced Humeral Shaft Fractures and the Need for Secondary Surgery

Abstract: IMPORTANCEExisting evidence indicates that surgery fails to provide superior functional outcome over nonoperative care in patients with a closed humeral shaft fracture. However, up to one-third of patients treated nonoperatively may require secondary surgery.OBJECTIVE To compare the 2-year outcomes of patients who required secondary surgery with the outcomes of patients with successful initial treatment. DESIGN, SETTING, AND PARTICIPANTSThis 2-year follow-up of the Finnish Shaft of the Humerus (FISH) randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Broadbent et al 18 also observed that humeral diaphyseal nonunion was associated with a worse Neer score up to 1-year postinjury. Reporting 2-year follow-up of the Finnish Shaft of Humerus (FISH) randomized clinical trial, Rämö et al 20 found that functional outcomes among 14 patients who united after nonunion surgery were inferior to those who underwent successful initial operative or nonoperative management. Our results add to this growing body of evidence that poorer function and HRQoL may persist for years following a humeral shaft nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadbent et al 18 also observed that humeral diaphyseal nonunion was associated with a worse Neer score up to 1-year postinjury. Reporting 2-year follow-up of the Finnish Shaft of Humerus (FISH) randomized clinical trial, Rämö et al 20 found that functional outcomes among 14 patients who united after nonunion surgery were inferior to those who underwent successful initial operative or nonoperative management. Our results add to this growing body of evidence that poorer function and HRQoL may persist for years following a humeral shaft nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…15,18,21 Longer-term patient-reported outcomes after a humeral diaphyseal fracture and the legacy of humeral shaft nonunion surgery are incompletely understood. 20 The authors are aware of only 2 smaller studies assessing factors associated with functional outcome, 18,19 and neither examines the effect of nonunion in the longer term.…”
Section: Introductionmentioning
confidence: 99%
“… 24 In the absence of any clear benefit, it has been difficult to justify the operative risks and increased costs associated with routine fixation for patients with these injuries. However, considering the differential nonunion rate between nonoperative and operative management, 6 , 7 and the increasing body of evidence that humeral shaft nonunion leads to inferior patient-reported upper limb function and health-related quality of life even after successful nonunion surgery, 8 , 9 there may be longer-term advantages to operative fixation that have been previously underappreciated. This study attempts to quantify the longer-term utility of reducing the risk of humeral shaft nonunion, by offering early surgery to all patients.…”
Section: Discussionmentioning
confidence: 99%
“…recalcitrant nonunion rate negligible); initial operative management involving plate and screw fixation would generate fracture union (i.e. nonunion rate after initial fixation negligible); longer-term HRQoL (according to the EQ-5D-3L) would be equivalent after initial nonoperative and initial operative management, provided union had been achieved; 3 , 4 , 8 , 9 and any difference in longer-term HRQoL (according to the EQ-5D-3L) resulting from nonunion after nonoperative management would be present throughout the preceding five years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation